Model for assessing the quality of marketing-management education - Rivera, Jaime (2020)
Purpose: This study aims to propose and test a model of educational quality in marketing-management by incorporating resource-capability variables that are linked to learning outcomes for students and the competitive positioning of universities. Design/methodology/approach – Drawing on the resource-dependence theory this study develops a comprehensive model for measuring educational quality. A sample comprising Spanish university teachers has been used to test the hypothesised relationships by using a two-stage least squares regression analysis while controlling for the possible effect of the public/private nature of the university. Findings – The results validate the model and show that educational capabilities are reliable variables for predicting the educational quality of marketing-management programmes at Spanish universities. Research limitations/implications – Similar to all educational research studies certain problems have been acknowledged with respect to the data and the theoretical constructs that are used in the study. Future studies can replicate this study’s model by using more direct objective measures of the theoretical constructs and extend the study to other countries with different educational contexts. Practical implications – The results provide guidance to marketing teachers at a university in designing high-quality marketing-management educational programmes and in developing self-diagnostic tools that can determine a university’s likelihood of competitive success. Originality/value – This study is one of the few studies to apply the resource-dependence theory to the analysis of the variables associated with the quality of marketing-management education. In doing so the study presents original multiitem scales to improve the measurement of model constructs.